Copper Keplerates: High‐Symmetry Magnetic Molecules. Issue 1 (16th November 2015) - Palacios, Maria A.; Moreno Pineda, Eufemio; Sanz, Sergio; Inglis, Ross; Pitak, Mateusz B.; Coles, Simon J.; Evangelisti, Marco; Nojiri, Hiroyuki; Heesing, Christian; Brechin, Euan K.; Schnack, Jürgen; Winpenny, Richard E. P.
Abstract: Keplerates are molecules that contain metal polyhedra that describe both Platonic and Archimedean solids; new copper keplerates are reported, with physical studies indicating that even where very high molecular symmetry is found, the low‐temperature physics does not necessarily reflect this symmetry. Abstract : New copper keplerates are reported, with physical studies indicating that even where very high molecular symmetry is found, the low‐temperature physics does not necessarily reflect this symmetry